2013
DOI: 10.1111/bjd.12586
|View full text |Cite
|
Sign up to set email alerts
|

Favourable prognostic role of regression of primary melanoma in AJCC stage I-II patients

Abstract: We confirmed that regression alone should not be a reason to perform SLNB in thin melanoma and, on the contrary, it can be considered a favourable prognostic factor in patients with AJCC stage I-II melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 25 publications
4
62
0
1
Order By: Relevance
“…7,72,[74][75][76]78,[100][101][102][103] On the other hand, additional studies have suggested that regression indicates a favorable outcome (Table 3). 3,[104][105][106][107][108] Thus, the prognostic significance of regression in primary melanoma has been controversial for many years. In the next section, we discuss some of the most relevant published studies with respect to melanoma recurrence, lymph node metastasis, and survival.…”
Section: Prognostic Significance Of Regression In Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…7,72,[74][75][76]78,[100][101][102][103] On the other hand, additional studies have suggested that regression indicates a favorable outcome (Table 3). 3,[104][105][106][107][108] Thus, the prognostic significance of regression in primary melanoma has been controversial for many years. In the next section, we discuss some of the most relevant published studies with respect to melanoma recurrence, lymph node metastasis, and survival.…”
Section: Prognostic Significance Of Regression In Melanomamentioning
confidence: 99%
“…4 Only a few studies have reported an association between the presence of regression and better survival rates. 104,108 Notably, most of these studies compared the presence or absence of late-stage regression, while some of the remaining studies compared the extent of regression as focal, partial, or complete or the stage of regression as early vs late or active vs past, with or without an intermediate stage. Only rare studies have examined regression further by measuring the depth of regression-associated fibrosis; Sondergaard and Hou-Jensen 75 expanded their analysis of regression by assessing the horizontal width and depth of fibrosis.…”
Section: Association Between Regression and Survivalmentioning
confidence: 99%
“…Regression was described as playing a protective role for prognosis in a large group of early stage melanoma [35] . Histological regression can occur frequently in trunk melanoma compared to melanomas arising on other body areas [36] .…”
mentioning
confidence: 99%
“…It was also suggested that the same therapeutic approach should be followed for both of these entities [12] . Furthermore, histological regression has been described as a potential favorable feature of melanoma as it probably reflects an activation of the immune system [13] . On the other hand, discordant data are reported regarding the survival of patients with complete regressed primary cutaneous melanoma [14] .…”
Section: Discussionmentioning
confidence: 99%